Training program for trainers in gender education of the angolan women's organization (Impetus, 2021)
Overcoming discrimination against women is an essential element for the construction of a truly democratic society, founded on respect for the rights of the person and human dignity. In Angolan society there are sexist communities that discriminate against women; Therefore, the work of the gender mobilizers and promoters is very much done, which is why a special preparation is necessary that includes other forms and techniques through the use of free time, which, as it was found, exists until now. This program proposes, through a system of techniques based on popular education, to offer a contribution to education and the gender approach in current Angolan society.
Keywords: trainers; education; gender; popular; free time